Sintesis Zat Warna Prussian Blue Fe4[Fe(CN)6]3 Berbahan Pasir Besi Alam - Muthiara Wahyuni; Syamsi Aini (Departemen Kimia FMIPA UNP, 2021)
Sijunjung iron sand has different chemical composition and properties and high magnetic susceptibility compared to other iron sands in West Sumatra so it requires different reaction conditions. The existing iron sand needs to be increased in economic value by using it as a basic material for the manufacture of dyes. Several dyes such as red, yellow and black have been synthesized which are based on iron sand. Prussian Blue with the formula Fe4[Fe(CN)6]3 was synthesized so that all the basic colors are met. Prussian Blue was synthesized by coprecipitation method at room temperature by varying the mass of K4[Fe(CN)6]. The addition of the K4[Fe(CN)6] mass makes the resulting color brighter and closer to the standard Prussian blue. The synthesized products characterized using the Prussian Blue UV-Vis Spectrophotometer did not meet the standards because some unwanted peaks appeared indicating the resulting material was impure, while characterization using FTIR could identify the presence of Prussian Blue-forming groups.